A mobile urine analysis system for homecare - Kahraman, Büşra. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 2013., 2013)
Urinalysis is a remarkable diagnostic technique and an essential part of physical examination used frequently in kidney and urinary tract diseases. Urine reagent strips which are widely used in urinalysis are impregnated with a number of colored reagent blocks or pads separated from each other by narrow bands. The reagents in each block react with speci c components of urine in such a way that the block changes color if the component is present, and the color change produced is proportional to the concentration of the component being tested for. Recent analysis of test strips is perfomed via refractometric devices of the corresponding test strips. In this thesis, a mobile urine strip analyzer called BUSA which can be controlled via both GUIs of MATLAB and Android operation system was designed by using Parallax's color sensor, TCS3200-DB. The fundemental idea behind this design was to form a database which included color data of control solutions of CombiScan 500, 40 patients analyzed by CombiScan 500 in Yeditepe University Hospital and prepared solutions of known pH and glucose amount. 15 patients analyzed by CombiScan 500 were compared to BUSA. Speci city of the results of the comparison for bilirubin, urobilinogen, glucose, protein, blood, nitrite and leukocyte was 1 and for ketone was 0.933. Sensitivty of the results of the comparison for glucose, protein and blood was 1, 0.2 and 1 respectively. pH and speci c gravity were analyzed via Blant Altman method which means and standard deviations were 0.133, 0.5156 and 0.0017, 0.0059 respectively. In conclusion, BUSA is succesful at measuring pH and specific gravity of urine and negativeness of bilirubin, urobilinogen, ketone, glucose, protein, blood, nitrite and leukocytes. In addition, BUSA is successful at detecting positiveness of glucose and blood, except protein.|Keywords : Urinalysis, Color sensor, Android, homecare.
Keywords: Urine -- Analysis.; Android.